Analysis of Foreign Investment Policy from the Perspective of Economic Development Law (Case Study: The New National Capital Nusantara) - Herlambang, Embang; Setiady, Tri (Universitas Muhammadiyah Tangerang, 2024)
Foreign investment plays a crucial role in driving a nation's economic growth. It involves capital investments by international investors into various sectors of a country's economy. In qualitative research on policy and law, data collection methods often include the analysis of official documents such as laws, government regulations, financial reports, and previous studies related to foreign investment and economic development in Indonesia's new national capital. Law No. 25/2007 concerning investors also reflects the significant impact of foreign investment on Indonesia's economic growth. Foreign sinvestment can stimulate growth through several mechanisms, such as increasing investment in sectors with a high multiplier effect, creating jobs, facilitating technology and management knowledge transfer, and enhancing the competitiveness of domestic products in the global market. The legal aspects of economic development play a key role in regulating and protecting foreign investments. Legal protection of intellectual property rights, ownership rights, and safeguarding investments from potential risks provides added security for foreign investors. Keywords: Investment, Policy, Economy